Exploration and Practice of AI Teaching Mode for Financial Management Course Based on Xuexitong - Feng, Jing; Huang, Xiqi; Li, Jingjing (Journal of Research in Vocational Education, 2025)
Driven by the digital wave, artificial intelligence technology is integrating into the field of education at an unprecedented speed and depth, bringing unprecedented opportunities for the innovation of teaching models. As a discipline that combines practicality and applicability, Financial Management shoulders the responsibility of providing high-quality financial management talents with solid theoretical foundations and excellent practical skills to society. However, traditional teaching methods have many shortcomings in stimulating students’ learning enthusiasm and meeting their personalized learning needs. Therefore, exploring how to effectively integrate AI technology into the teaching of financial management courses is not only an important issue faced by educators, but also a key factor in promoting financial management education to keep pace with the times and adapt to the needs of social development. This article aims to explore the application strategies of AI technology in the teaching of financial management courses, as well as its positive impact on students’ learning interest and ability improvement, providing useful reference and inspiration for the reform of financial management course teaching in universities.